Ecotonal gradients shape biodiversity of multiple estuarine taxa - Rebecca Oester; Benjamin Branoff; Johanna Biederbick; Luise Grüterich; Raphael Koll; Fay Lexmond; Nele Martens; Julian Mittmann-Goesele; Friederike Neiske; Widhi Putri; Sina Remmers; Diana Richter; et al. (Estuarine, Coastal and Shelf Science, 2026)

GWAS reveals genomic associations with swine inflammation and necrosis syndrome - Katharina Gerhards; Sabrina Becker; Josef Kuehling; Mirjam Lechner; Jochen Bathke; Hermann Willems; Gerald Reiner (Mammalian Genome, 2023)
The recently identified swine inflammation and necrosis syndrome (SINS) occurs in high prevalence from newborn piglets to fattening pigs and resembles an important concern for animal welfare. The primary endogenous syndrome affects the tail, ears, teats, coronary bands, claws and heels. The basis of clinical inflammation and necrosis has been substantiated by histopathology, metabolomic and liver transcriptomic. Considerable variation in SINS scores is evident in offspring of different boars under the same husbandry conditions. The high complexity of metabolic alterations and the influence of the boar led to the hypothesis of a polygenic architecture of SINS. This should be investigated by a genome-wide association study. For this purpose, 27 sows were simultaneously inseminated with mixed semen from two extreme boars. The mixed semen always contained ejaculate from a Pietrain boar classified as extremely SINS susceptible and additionally either the ejaculate from a Pietrain boar classified as SINS stable or from a Duroc boar classified as SINS stable. The 234 piglets were phenotyped on day 3 of life, sampled and genetically assigned to the respective boar. The piglets showed the expected genetic differentiation with respect to SINS susceptibility. The suspected genetic complexity was confirmed both in the number and genome-wide distribution of 221 significantly associated SNPs, and led to 49 candidate genes. As the SNPs were almost exclusively located in noncoding regions, functional nucleotides have not yet been identified. The results suggest that the susceptibility of piglets to SINS depends not only on environmental conditions but also on genomic variation.

Impact of weathered multi-walled carbon nanotubes on the epithelial cells of the intestinal tract in the freshwater grazers Lymnaea stagnalis and Rhithrogena semicolorata - Katrin Weise; Thomas Kurth; Anna Schmidt; Carola Winkelmann; Jochen Becker; Susanne Kretschmar; Thomas Ulrich Berendonk; Dirk Jungmann (Environmental Science and Pollution Research, 2023)
Freshwater grazers are suitable organisms to investigate the fate of environmental pollutants, such as weathered multi-walled carbon nanotubes (wMWCNTs). One key process is the uptake of ingested materials into digestive or absorptive cells. To address this, we investigated the localization of wMWCNTs in the intestinal tracts of the mud snail Lymnaea stagnalis ( L. stagnalis ) and the mayfly Rhithrogena semicolorata ( R. semicolorata ). In L. stagnalis , bundles of wMWCNTs could be detected in the midgut lumen, whereas only single wMWCNTs could be detected in the lumina of the digestive gland. Intracellular uptake of wMWCNTs was detected by transmission electron microscopy (TEM) but was restricted to the cells of the digestive gland. In larvae of R. semicolorata , irritations of the microvilli and damages in the apical parts of the epithelial gut cells were detected after feeding with 1 to 10 mg/L wMWCNTs. In both models, we detected fibrillar structures in close association with the epithelial cells that formed peritrophic membranes (PMs). The PM may cause a reduced transmission of wMWCNT bundles into the epithelium by forming a filter barrier and potentially protecting the cells from the wMWCNTs. As a result, the uptake of wMWCNTs into cells is rare in mud snails and may not occur at all in mayfly larvae. In addition, we monitor physiological markers such as levels of glycogen or triglycerides and the RNA/DNA ratio. This ratio was significantly affected in L. stagnalis after 24 days with 10 mg/L wMWCNTs, but not in R. semicolorata after 28 days and 10 mg/L wMWCNTs. However, significant effects on the energy status of R. semicolorata were analysed after 28 days of exposure to 1 mg/L wMWCNTs. Furthermore, we observed a significant reduction of phagosomes per enterocyte cell in mayfly larvae at a concentration of 10 mg/L wMWCNTs ( p < 0.01).

Use of an INLA Latent Gaussian Modeling Approach to Assess Bird Population Changes Due to the Development of Offshore Wind Farms - Raul Vilela; Claudia Burger; Ansgar Diederichs; Fabian E. Bachl; Lesley Szostek; Anika Freund; Alexander Braasch; Jochen Bellebaum; Brian Beckers; Werner Piper; Georg Nehls (Frontiers in Marine Science, 2021)
The utilization of marine renewable energies such as offshore wind farming leads to globally expanding human activities in marine habitats. While knowledge on the responses to offshore wind farms and associated shipping traffic is accumulating now at a fast pace, it becomes important to assess the population impacts on species affected by those activities. In the North Sea, the protected diver species Red-throated Diver ( Gavia stellata ) and Black-throated Diver ( Gavia arctica ) widely avoid offshore wind farms. We used an explicit spatio-temporal Bayesian model to get a robust estimate of the diver population during the spring season between 2001 and 2018, based on a set of aerial surveys from long-term monitoring programs within the German North Sea. Despite the erection of 20 offshore wind farms in the study area and marked responses of divers to wind farms, model results indicated that there was no population decline, and overall numbers fluctuated around 16,600 individuals, with average annual 95% CI ranging between 13,400 and 21,360 individuals. Although, avoidance behavior due to wind farm development led to a more narrowly focused spatial distribution of the birds centered in the persistent high concentration zone in the Eastern German Bight Special Protection Area, the results provide no indication of negative fitness consequences on these long-lived species. However, more research is needed on habitat use and food availability in this regard.

Geometallurgical Approach for Implications of Ore Blending on Cyanide Leaching and Adsorption Behavior of Witwatersrand Gold Ores, South Africa - Glen T. Nwaila; Yousef Ghorbani; Megan Becker; Hartwig E. Frimmel; Jochen Petersen; Steven Zhang (Natural Resources Research, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Fall Risk in Relation to Individual Physical Activity Exposure in Patients with Different Neurodegenerative Diseases: a Pilot Study - Karin Srulijes; Jochen Klenk; Michael Schwenk; Cornelia Schatton; Lars Schwickert; Kristin Teubner-Liepert; Miriam Meyer; Srijana K.C.; Walter Maetzler; Clemens Becker; Matthis Synofzik (The Cerebellum, 2019)

Fgf9 Y162C Mutation Alters Information Processing and Social Memory in Mice - Lillian Garrett; Lore Becker; Jan Rozman; Oliver Puk; Tobias Stoeger; Ali Önder Yildirim; Alexander Bohla; Oliver Eickelberg; Wolfgang Hans; Cornelia Prehn; Jerzy Adamski; Thomas Klopstock; et al. (Molecular Neurobiology, 2018)

The very hungry amphipod: the invasive Dikerogammarus villosus shows high consumption rates for two food sources and independent of predator cues - Luise Richter; Lisa Schwenkmezger; Jochen Becker; Carola Winkelmann; Claudia Hellmann; Susanne Worischka (Biological Invasions, 2018)

Larval growth and metabolic energy storage of Micropterna lateralis (Trichoptera: Limnephilidae) in an intermittent stream: glycogen dominates in final instars - Felicitas Hoppeler; Carola Winkelmann; Jochen Becker; Steffen U. Pauls (Hydrobiologia, 2018)

River-specific effects of the invasive amphipod Dikerogammarus villosus (Crustacea: Amphipoda) on benthic communities - Claudia Hellmann; Franz Schöll; Susanne Worischka; Jochen Becker; Carola Winkelmann (Biological Invasions, 2017)

Effects of two elongation factor 1A isoforms on the formation of gephyrin clusters at inhibitory synapses in hippocampal neurons - Michal Becker; Jochen Kuhse; Joachim Kirsch (Histochemistry and Cell Biology, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

Physiological indicators of fitness in benthic invertebrates: a useful measure for ecological health assessment and experimental ecology - Jochen H. E. Koop; Carola Winkelmann; Jochen Becker; Claudia Hellmann; Christian Ortmann (Aquatic Ecology, 2011)

Identification of differentially expressed small non-protein-coding RNAs in Staphylococcus aureus displaying both the normal and the small-colony variant phenotype - Luay F. Abu-Qatouseh; Suresh V. Chinni; Jochen Seggewiß; Richard A. Proctor; Jürgen Brosius; Timofey S. Rozhdestvensky; Georg Peters; Christof von Eiff; Karsten Becker (Journal of Molecular Medicine, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

New editorial office - Heiko C. Becker; Christian Möllers; Albrecht E. Melchinger; Eva Bauer; Jochen C. Reif (Theoretical and Applied Genetics, 2005)